Price adjustment in German manufacturing: evidence from two merged survey - Harald Stahl (Deutsche Bundesbank, 2006)
This paper presents new evidence on the formation of producer prices. The database combines a one-time survey that was conducted in June 2004 on a sample of 1,200 firms in manufacturing and time-series information on price adjustment of the same firms from a business-tendency survey. The share of time-dependent price setters amounts to 20 per cent. Neither Taylor nor Calvo type price setting describes their price adjustment well. Only a few firms are forward-looking, the majority relies on contemporaneous and past information.
Keywords: E30; D40; 330; Price rigidity; sticky information; survey data; Preisrigidität; Industrieprodukt; Industriepreisindex; Schätzung; Deutschland